Interpreting the Temporal Dynamics of Perceptual Rivalries. (November 2014) - Gallagher, Regan M; Arnold, Derek H
Diverse forms of perceptual rivalry are claimed to tap a common causal mechanism. One of the bases for this claim is that the reported dynamics of binocular rivalry and motion-induced blindness are similar on an individual basis (Carter & Pettigrew, 2003 Perception, 32, 295–305). We examined this relationship and found no evidence for a strong correlation. We therefore question the proposition that the dynamics of diverse forms of rivalry are driven by a common mechanism.